2015
DOI: 10.1080/17458080.2014.994680
|View full text |Cite
|
Sign up to set email alerts
|

Rapid synthesis of highly stable silver nanoparticles and its application for colourimetric sensing of cysteine

Abstract: A modified green approach for the synthesis of stable silver nanoparticles (AgNPs) using tea leaf extract is described. The method involves the reduction of silver salt by the polyphenols present in the green tea leaf extract and requires no additional capping/stabilising agents. Compared to other biogenic methods for the synthesis of AgNPs, the uniqueness of the approach described here lies in its simplicity, low-cost, and rapid synthesis rate; the reaction being completed within 10À15 min at room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…However as the yield of AgNPs increases, aggregation is likely to occur due to increase in the collision frequency of nanoparticles [16]. Earlier reports have also suggested that plant extract based synthesis of AgNPs requires longer time and highlighted it as one of the major limitation [2]. While, in the studies conducted by Shameli et al , [17] the reaction time required for AgNPs synthesis was 1 h. Similarly, Murgan et al [18] working with Acacia leucopholea took 1 h and 10 min at 90°C for AgNPs synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However as the yield of AgNPs increases, aggregation is likely to occur due to increase in the collision frequency of nanoparticles [16]. Earlier reports have also suggested that plant extract based synthesis of AgNPs requires longer time and highlighted it as one of the major limitation [2]. While, in the studies conducted by Shameli et al , [17] the reaction time required for AgNPs synthesis was 1 h. Similarly, Murgan et al [18] working with Acacia leucopholea took 1 h and 10 min at 90°C for AgNPs synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Metallic nanoparticles have found application in a plethora of fields that includes photonics, catalysis, bio‐imaging, environment remediation and drug delivery [1, 2]. Amongst metallic nanoparticles, silver nanoparticles (AgNPs) have emerged as one of the major potential candidates owing to their ease of synthesis, stability, biocompatibility and low toxicity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs) provide excellent platforms for the development of colorimetric biosensors as they can be easily functionalised displaying different colours depending on their size, shape and state of aggregation [12]. The conventional method for the synthesis of AuNPs involves the reduction of gold ions by reducing agents such as alkanethiols and alkylamines, or polymeric materials such as polyvinyl alcohol and gelatin to stabilise the AuNPs from aggregation [13]. However the use of capping agents for stabilisation and toxic chemicals for reductions may result in the formation of hazardous by-products, adversely affecting their use in diagnostics [14].…”
Section: Methods Detailsmentioning
confidence: 99%
“…Using a simple dilution, the observed color of particles with the same size and shape can change from, for example, dark orange to bright yellow. Moreover, λ max will not change by dilution, but a decrease in the absorbance at this λ max will be observed [51,52].…”
Section: Uv-vis Spectroscopy and Visual Analysismentioning
confidence: 98%